Learning and teaching sustainability: The contribution of Ecological Footprint calculators. (10th February 2018) - Collins, Andrea; Galli, Alessandro; Patrizi, Nicoletta; Pulselli, Federico Maria
Abstract: Consumption habits imply responsibility. Progressive awareness of the scale of materials, energy, goods and services consumed on a daily basis and knowledge of the implications of consumption choices are prerequisites for designing steps towards sustainable behavior. This article explores, for the first time, the educational value of personal Footprint calculators and their contribution in terms of enhancing awareness of the environmental consequences of consumption behaviors. Our study involved the application of Global Footprint Networks' personal Ecological Footprint (EF) calculator in teaching aimed at High School and postgraduate University students in two geographical areas (Italy and UK). Students calculated their individual EF, and used the results to explore the environmental consequences of their current consumption behaviors and the effects associated with selected changes in daily consumption activities. Our analysis shows that students were able to appreciate the difference between their individual Footprints and national and global averages. The calculator also enabled them to debate sustainable consumption in the context of their everyday life, inducing them to personally experience the multidimensional character of sustainability. Students finally demonstrated an ability to quantitatively capture how knowledge and awareness of the environmental consequences associated with certain consumption behaviors may facilitate better choices, and encourage greater commitment to sustainable resource use. Highlights: Ecological Footprint (EF) has gained a prominent position in the sustainability debate since its introduction. We used a personal Footprint calculator to teach environmental aspects of sustainability. Students experienced at firsthand the multidimensional character of sustainability. They gained insight on how daily activities affect the global sustainability discourse. Our experiment is an effective way to initiate participative discussions on environmental sustainability.